Predictors of Diabetes Self-Care Practice Among Patients with Type 2 Diabetes in Public Hospitals in Northeastern Ethiopia: A Facility-Based Cross-Sectional Study - Gulentie, Tesfaye Molla (Diabetes Metab Syndr Obes, 2020)
OBJECTIVE: Even though life-threatening complications in type 2 diabetes mellitus (T2DM) minimize through self-care practice, extensive studies in northeast Ethiopia have been scarce about self-care practice and predictors. This study aimed to assess diabetes self-care predictors among patients with T2DM patients at Dubti and Assaita hospitals in northeastern Ethiopia. METHODS: A facility-based cross-sectional study was conducted among 403 patients with T2DM who followed-up in northeastern Ethiopia’s Dubti and Assaita hospitals. Data were analyzed using SPSS version-22.0 after the data were entered, sorted and cleaned. Multiple stepwise backward logistic regression analysis was done for a P value of <0.25 to identify the independent predictors of self-care practice. RESULTS: In the present study, males comprised 62% of the sex category. Overall, 63.8% of the study participants had adequate self-care practice, while 36.2% had inadequate self-care practice. Being younger age (AOR 2.27, 95% CI 1.27–4.07, P= 0.005), monthly income status with low (AOR 3.08, 95% CI 1.08–8.78, P= 0.04), average (AOR 2.43, 95% CI 1.15–5.09, P= 0.02) and high (AOR 2.68, 95% CI 1.03–6.99, P= 0.04), treated with oral hypoglycemic agents (OHA) (AOR 0.22, 95% CI 0.05–0.95, P = 0.04) and insulin (AOR 0.18, 95% CI 0.04–0.75, P= 0.01), having social support (AOR 3.09, 95% CI 1.76–5.4, P ≤ 0.01) and diabetic education from health professionals (AOR 5.53, 95% CI 1.92–15.93, P= 0.001) and media (AOR 2.63, 95% CI 1.47–4.7, P = 0.001) were the independent predictors of self-care practice. CONCLUSION: In this study, the practice of self-care found to be sub-optimal among patients with T2DM. Independent predictors of self-care practice were age, monthly income, treatment regimen, social support, and diabetic education. Therefore, a suitable approach should be built to improve self-care practice with diabetes.